2007
DOI: 10.1590/s1413-86702007000100028
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the national nosocomial infections surveillance system risk index for the prediction of surgical site infections: a review

Abstract: . The types of surgical procedures for which the NNIS index has proven to be an efficient system for the classification of patients are presented. The necessity of adapting the NNIS index to take into account specific characteristics associated with hospitals and practices in various regions and countries is stressed. The requirement for further testing and development of the rate concerning specific procedures, particularly those involving orthopaedic surgery, is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 49 publications
1
17
1
4
Order By: Relevance
“…The report of present study coincides with the findings of Ercole FF et al and was also found statistically significant. 18 Use of perioperative antibiotics did not have any impact on reduction of SSI in present study and was also found not statistically significant. This can be explained by the fact that absence of clear antibiotic policy in administration during surgery.…”
Section: Discussioncontrasting
confidence: 51%
“…The report of present study coincides with the findings of Ercole FF et al and was also found statistically significant. 18 Use of perioperative antibiotics did not have any impact on reduction of SSI in present study and was also found not statistically significant. This can be explained by the fact that absence of clear antibiotic policy in administration during surgery.…”
Section: Discussioncontrasting
confidence: 51%
“…The CDC criteria 11 were used to diagnose SSI. The information were stored in a database and analyzed using the software SPSS for Windows, release 17.0.…”
Section: Methodsmentioning
confidence: 99%
“…Gram negative bacilli (Klebsiella, Pseudomonas and Escherichia coli) were the commonest organisms cultured in this study which reflects the predominance of SSI in abdominal and perineal operations. An operation duration of longer than 2 hour has been reported to be associated with SSI 18,19 . This was demonstrated in this study where operation of more than 2 hours was significantly associated with SSI (P= 0.02).…”
Section: Discussionmentioning
confidence: 99%